A man completely devoid of falsehood?: creating credibility in Gregory Nazianzen’s autobiographical poems - Kuhn-Treichel, Thomas (Vigiliae Christianae, 2020)
Gregory of Nazianzus is an important case study for the development of autobiography, not only because he is one of the first Christians to write extended autobiographical texts, but also because he does so in verse. This paper addresses two interwoven questions: which strategies does Gregory employ in his autobiographical poems in order to create credibility for his literary self, and which of the motifs that he uses are innovative or specific to his autobiographical poetry? I suggest that Gregory constructs credibility mainly through his relationships with different entities (persons, objects, ideas …) represented in the poems. In some of the relationships (e.g., with his opponents) one can find clear parallels with pagan poets while in others, specifically Christian elements come into play (sometimes blended with pagan traditions). Gregory’s most original idea appears in his relationship with his medium of communication, where one can find a justification for poetic autobiography as a genre.
Gesehen am 22.07.2020